THE IMPACT OF CHARISMATIC LEADERSHIP, ORGANIZATIONAL CULTURE, AND ORGANIZATIONAL COMMITMENT ON THE DISCIPLINE - Sanggarwati, Diah Ayu; Subiantoro, Bambang; Adi, Titok Waskito (Media Bina Ilmiah, 2024)
This study aims to examine the influence of charismatic leadership, organizational culture, and organizational commitment on discipline. It is a quantitative study with a saturated sample size of 50 members of the PSHT-Cabang Gresik Pencak Silat organization. Based on the analysis and hypothesis testing using SPSS 26 program, the results show that charismatic leadership, organizational culture, and organizational commitment have a significant influence on member discipline, both partially and simultaneously. This research contributes to the scholarly discourse on the specific topic, particularly in non-profit organizations